Does board usage of knowledge and skills affect internationalization performance of SMEs? A case of Lithuania - Bužavaitė, Monika; Korsakienė, Renata (Journal of Business Economics and Management, 2022)
Internationalization of SMEs is encouraged by the advantages of new environmental conditions and appealing business opportunities, but remains a challenging process. Top management teams and more specifically board of directors appear to be a critical determinant in addressing internationalization issues. In recent years, investigation of boards in small firms’ context has been an interest of scholars, however few investigated characteristics of human capital. This study aims to investigate whether board usage of knowledge and skills is a mediator linking characteristics of human capital of board and internationalization performance of SMEs in Lithuania. The results revealed that usage of knowledge and skills mediates the relationships between international business skills and internationalization performance. Obtained results contribute to international entrepreneurship and upper-echelons theories by highlighting the role of the board in SMEs and linking it to higher internationalization performance through their usage of knowledge and skills. This study fills the research gap and extends the extant studies in internationalization of SMEs. First, the study responds to the need to investigate how board’s capital affect internationalization. Secondly, the study responds to the need to go beyond input-output models. First published online 14 December 2021